Analisis Bibliometrik: Peran Humas Perguruan Tinggi - Daud, Yusri M (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the role of public relations in higher education through a bibliometric analysis approach. The research gap identified in this study is the limited comprehensive study that specifically links the results of bibliometric analysis with the strategic role of public relations in building an image, reputation, and institutional communication in the higher education environment. This study uses a bibliometric analysis method based on Google Scholar indexed article data collected through the Publish or Perish (PoP) software in the period 2020–2025, with a maximum of 1000 relevant articles. Data processing is done using Microsoft Excel and visual mapping is done through the VOSviewer application. Analysis was carried out on publication trends, keyword distribution, and thematic linkages through overlay and density visualization. The results of the study show that the main themes that dominate the literature on the role of public relations in higher education are